Influence of the nutritional level and pre-sowing seed treatment on the yield of spring wheat - Amirov Marat (EDP Sciences, 2021)
It remains relevant to meet the needs of plants in nutrients, methods of using growth stimulants, considering the active phases of culture development. The purpose of our research is to study the complex effect of the level of mineral nutrition, pre-sowing treatment of seeds, and spraying growing plants with a growth regulator on the productivity of spring wheat. Laboratory research and field experiments were carried out in 2019–2020 based on the Federal State Budgetary Educational Institution in the field of Higher Education "Kazan State Agrarian University" on gray forest soil. The average yield of spring wheat over the years of research against the background without fertilizers was 3.94 t/ha, against the background of NPK to obtain 3.5 t/ha of grain – 4.53 t/ha, against the background of NPK to obtain 4.5 t/ha of grain – 5.24 t/ha. The complex use of growth stimulants during pre-sowing seed treatment and double spraying in the tillering phase and spring wheat into the tube contributed to an increase in yield in all nutritional backgrounds by another 4.9–6.3 %.